2019
DOI: 10.3847/2041-8213/ab5dc6
|View full text |Cite
|
Sign up to set email alerts
|

The Chemical Signatures of Planetary Engulfment Events in Binary Systems

Abstract: Planetary engulfment events involve the chemical assimilation of a planet into a star's external layer. This can cause a change in the chemical pattern of the stellar atmosphere in a way that mirrors the composition of the rocky object engulfed, with the refractory elements being more abundant than the volatiles. Due to these stellar chemical changes, planetary engulfment events can render the process of chemical tagging potentially inaccurate. A line-by-line differential analysis of twin stars in wide binary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 52 publications
2
25
0
Order By: Relevance
“…We also include two pairs (HD 98744/45 and HIP 70386A/B) from Nagar, Spina & Karakas (2020) for examination, because both pairs show overall abundance offsets but no T cond trends. We found that the observed differences in [Fe/H] agree with the theoretical models for four of our pairs (HD 108574/75, HD 146368A/B, HD216122A/B and HIP 92961/62) and one pair (HD 98744/45) from Nagar, Spina & Karakas (2020), all with log g differences exceeding 0.05 dex.…”
Section: Effects Of Atomic Diffusionsupporting
confidence: 83%
See 1 more Smart Citation
“…We also include two pairs (HD 98744/45 and HIP 70386A/B) from Nagar, Spina & Karakas (2020) for examination, because both pairs show overall abundance offsets but no T cond trends. We found that the observed differences in [Fe/H] agree with the theoretical models for four of our pairs (HD 108574/75, HD 146368A/B, HD216122A/B and HIP 92961/62) and one pair (HD 98744/45) from Nagar, Spina & Karakas (2020), all with log g differences exceeding 0.05 dex.…”
Section: Effects Of Atomic Diffusionsupporting
confidence: 83%
“…These studies favour the M09 scenario, where they found the planet-hosting stars are depleted in refractory elements. Meanwhile, Saffe et al (2017); Oh et al (2018); Ramírez et al (2019) and Nagar, Spina & Karakas (2020) have studied several binary systems and found that one of the binary components exhibits a significant increase in elemental abundances (0.1 -0.2 dex) of e.g., HAT-P-4 system, HD 240430/29 and HIP 34407/26. They tentatively attributed the large abundance differences to the effects of planet engulfment.…”
Section: Introductionmentioning
confidence: 99%
“…The code delivers the EW of each line of interest along with its uncertainty. The same method for the EW measurement was employed in the high-precision spectroscopic analysis of twin stars by Nagar et al (2020).…”
Section: Stellar Parameters and Chemical Abundancesmentioning
confidence: 99%
“…Under the reasonable and common assumption that the components of binary systems share their initial composition (e.g., Desidera et al 2006;Andrews et al 2019;Hawkins et al 2020;Nelson et al 2021), since they form coevally from the same molecular cloud, it is unlikely that their dissimilar abundances are caused by different Galactic chemical evolution (e.g., Adibekyan et al 2014;Nissen 2015) or different stellar environment effects (e.g., Önehag et al 2014). Alternatively, as discussed in several previous studies of binary stars with similar components, the elemental abundance differences might be connected to processes of planetary formation and evolution (e.g., Ramírez et al 2011Ramírez et al , 2015Teske et al 2016a,b;Saffe et al 2015Saffe et al , 2017Oh et al 2018;Nagar et al 2020).…”
Section: Refined Planet Properties Of Wasp-160b Bmentioning
confidence: 89%